Alternate Furrow Irrigation: A Practical Way to Improve Grape Quality and Water Use Efficiency in Arid Northwest China - Tai-sheng DU; Shao-zhong KANG; Bo-yuan YAN; Jian-hua ZHANG (Journal of Integrative Agriculture)
Field experiments were conducted for two years to investigate the benefits of alternate furrow irrigation on fruit yield, quality and water use efficiency of grape (Vitis vinifera L. cv. Rizamat) in the arid region of Northwest China. Two irrigation treatments were included, i.e., conventional furrow irrigation (CFI, two root-zones were simultaneously irrigated during the consecutive irrigation) and alternate partial root-zone furrow irrigation (AFI, two root-zones were alternatively irrigated during the consecutive irrigation). Results indicate that AFI maintained similar photosynthetic rate (Pn) but with a reduced transpiration rate when compared to CFI. As a consequence, AFI improved water use efficiency based on evapotranspiration (WUEET, fruit yield over water consumed) and irrigation (WUEI, fruit yield over water irrigated) by 30.0 and 34.5%, respectively in 2005, and by 12.7 and 17.7%, respectively in 2006. AFI also increased the edible percentage of berry by 2.91–4.79% significantly in both years. Vitamin C (Vc) content content of berry was increased by 25.6–37.5%, and tritrated acidity (TA) was reduced by 9.5–18.1% in AFI. This resulted in an increased total soluble solid content (TSS) to TA ratio (TSS/TA) by 11.5–16.7% when compared to CFI in both years. Our results indicate that alternate furrow irrigation is a practical way to improve grape fruit quality and water use efficiency for irrigated crops in arid areas.